Experience and Interpretation: Emotion as Revealed in Narration - Annikki Kaivola-Bregenhøj (Journal of Ethnology and Folkloristics)
I discuss in this article some key narratives of women I interviewed in Ingria 1992–1993. The narratives of those women were about dramatic stages of their lives during the World War II. The main themes of the life stories were forced transfers and deportation suffered by the Ingrian Finns. I examine with some examples how various paralinguistic devices, such as speech tempo, emotional outbursts or silence, were tied in with the verbalisation of experiences. The three factors I discuss here are woven into the narratives of the women I interviewed. The first factor is “impassioned narrating”, which shows how a narrator reveals how she is reliving the event, she told about. The second factor is weeping and we may ask how the tears affect the narrator. The third factor is silence and reticence. In retrospect I have thought about the therapeutic effect of speaking, forgetting and remaining silent.